Analisis Konsep Diri Siswa di SMAN 4 Kerinci - Julia Eva Putri (Peneliti.net, 2023)
The student's self-concept is the way how students see themselves which is related to physical, social, emotional, moral, and cognitive. This can be influenced by the social environment such as the family, community and school environment. Self-concept determines student behavior, therefore a positive self-concept is needed by students to develop their potential optimally. The technique in this study was descriptive quantitative with a sample of 83 people at SMAN 4 Kerinci. The results of the study show that students' self-concept is in a fairly good category, this needs to be maintained and can be improved through guidance and counseling services in schools